-10+8h-2=10h+8

Simple and best practice solution for -10+8h-2=10h+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+8h-2=10h+8 equation:



-10+8h-2=10h+8
We move all terms to the left:
-10+8h-2-(10h+8)=0
We add all the numbers together, and all the variables
8h-(10h+8)-12=0
We get rid of parentheses
8h-10h-8-12=0
We add all the numbers together, and all the variables
-2h-20=0
We move all terms containing h to the left, all other terms to the right
-2h=20
h=20/-2
h=-10

See similar equations:

| 8x-4=6x-20 | | 5k+1=-1 | | 2z-87=z+28 | | |4m+8|=16 | | -10+n/2=-3 | | 5x+3=-2(x-9) | | 2x-2-6x=4(2x+3) | | 1+7k+9k=10k+10-3 | | -4-3(-5+5r)=-40+2r | | -17x-14=-82-17x= | | 11=a9−6 | | v/2−–8=9 | | 4v=-10+6v | | 1/3(x+18)=10 | | 2x+5,4=4 | | 83-n=517 | | 7/100=3.5/x | | -10+5w=10w | | 4m-7=8m+9 | | .5n+26=50 | | v2−–8=9 | | n+2=4n-34 | | -10n+50=-10(4n+4) | | z–44+z–43=z+28 | | 2c+8=4c-8 | | 0,3•(x+5)-2=0,05•x | | 3x+5+5x-27=180 | | v2− –8=9 | | 2=k−52 | | 8=m—12 | | 5x4(x-1)=2x-9 | | -8(10x-1)-10=7-8(10x+1) |

Equations solver categories